Platelet Activating Properties of Murine Monoclonal Antibodies to β2-Glycoprotein I - Arvieux, J; Roussel, B; Pouzol, P; Colomb, M G (Thrombosis and Haemostasis, 1993)
Previously developed murine monoclonal antibodies (MAbs) to human β2-glycoprotein I (β2GPI), a plasma protein required for the binding of anti-phospholipid antibodies, were studied for anti-platelet reactivity and influence on platelet function. The six MAbs (IgG1 isotype) tested interacted with both intact and fixed platelets in a β2GPI-dependent manner. Carbamylated β2GPI was still recognized by MAbs but was unable to mediate platelet- antibody binding. MAbs induced aggregation and secretion responses of platelets in platelet-rich plasma (PRP) and whole blood, provided subthreshold concentrations of weak agonists (i.e. ADP or adrenaline) were added. When aggregation in PRP was evaluated by a counting technique instead of turbidometrically, the sole addition of MAbs led to a rapid fall in single platelets. Triggering gel-filtered platelets with MAbs together with β2GPI, but not its carbamylated form, led to platelet activation after a lag time, as monitored by aggregometry, measurements of ATP and β-thromboglobulin secretion and calcium mobilization. F(ab')2 fragments of one of the MAbs failed to activate platelets but inhibited the responses to the whole antibody. This process thus depends on MAbs binding to platelets through both Fab and Fc domains, as confirmed by the suppression of platelet responses upon pretreatment with the anti-FcγRII MAb IV.3. Aggregation and secretion induced by MAbs plus β2GPI did not require exogenous fibrinogen and were variably inhibited in the presence of acetyl salicylic acid, apyrase or Ca2+, depending on the concentrations used for the two proteins. We propose that platelet FcγRII crosslinking that follows a platelet-antibody interaction via the platelet binding protein, β2GPI, may be a new mechanism by which anti-β2 GPI antibodies activate platelets and/or synergize with weak agonists.